Heart rate variability analysis in exercise physiology - Hottenrott, K.; Hoos, O. (ECG Time Series Variability Analysis. Engineering and medicine, 2017)
The autonomous regulation of heart rate (HR) and its acute and chronic adaptation to exercise constitutes a classical and important field of cardiovascular research. Since the end of the twentieth century the application of heart rate variability (HRV) analysis in sports has grown in importance because of the introduction of accurate electrocardiogram (ECG) measurements of beat-to-beat variability with portable devices. Several epidemiological and population-based trials show that physical activity influences the autonomic nervous system. The majority of studies with a longitudinal design have investigated effects of endurance training in the short to medium term. Most of these interventions confirmed that moderate aerobic exercise in contrast to resistance training leads to increases of overall and vagal nerve-mediated HRV parameters at rest. The underlying mechanisms for the autonomic regulation of HR during exercise are the reduced parasympathetic and increased sympathetic modulation of the sinus node, which regulate nonpathological tachycardia during exercise.